Notes on Kempnyia, with the description of three new species (Plecoptera: Perlidae) - Froehlich, Claudio Gilberto (Illiesia, 2011)
Three new species of Kempnyia, K. kaingang sp. n., K. ocellata sp. n. and K. pinhoi sp. n., are described. Illustrations of the egg and female sterna 8-9 are presented for K. neotropica (Jacobsen and Bianchi). Kempnyia serrana (Navás) is recorded from the State of Sao Paulo. The female of K. petersorum Froechlich is described and a new illustration of the penial armature of that species is presented. New illustrations of the penial armature of K. tenebrosa Klapálek are also provided and a figure of the female sternum 9 of Nedanta fusca Navás is presented.
Keywords: entomology; Perlidae; Plecoptera; vrbnice; stonefly; nove vrste; Brazilija; Kempnyia; new species; comments on species; Brazil